Student Achievement and Government Intervention: What to Learn from Teresina, Piauí, Brazil - dos Santos, Kléber Montezuma Fagundes; Passos, Guiomar de Oliveira (European Scientific Journal, ESJ, 2018)
This text analyzes interventions by the Teresina municipal government to influence student performance, making test score results fall among the best of the Brazilian state capitals on assessments by the Anísio Teixeira National Institute for Educational Studies and Research (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira [INEP]) despite having the highest national proportion of the poor (27.6%). Using bibliographic data, the authors try to identify the factors favoring this performance. It was verified that Teresina implemented continuous and articulated actions, programs and projects, adopted a result and efficiency-based management model, introduced an evaluation and valorization merit system, measured and recognized in various ways. Educational policies and practices seem to follow a previously elaborated script in which each manager appropriates the actions of their predecessors, giving them continuity, perfecting and expanding them. In short, the public policies of each government were conditioned by preceding administrations. This had as its mainstay the longevity of the municipal government managed by the same political group, responsible for most of the organizational and educational policy initiatives, for the ideas and practices that characterized the performance of the municipal administration. The objective conditions offered by the new institutional framework, expressed by the political continuity, in combination with the subjective factors constitute the best explanations for understanding why the municipality of Teresina has become "a success story".